2014
DOI: 10.1111/1471-0528.13199
|View full text |Cite
|
Sign up to set email alerts
|

Stabilising the caesarean rate: which target population?

Abstract: Objective Caesarean rate increased in France between 1995 and 2003, but remained stable between 2003 and 2010. Our objective was to analyse these trends by identifying the groups of women who contributed to the increase and those who contributed to the stabilisation.Design Cross-sectional population-based study from the French national perinatal surveys.Setting All maternity units in France.Population Representative samples of women delivering in 1995 (n = 13 147), 2003 (n = 14 482), and 2010 (n = 14 681).Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
48
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 32 publications
(29 reference statements)
9
48
1
1
Order By: Relevance
“…The same authors also pointed out that the proportion of this group in the population was similar between institutions, reinforcing the hypothesis that there are variations in the CS rate in this group that affect the overall rate. In our study, the proportion of groups 1 and 2 combined was 39 %, similar to that found in Latin America (36.4 %) [31], France (38.2 %) [21], Canada (39.7 %) [30] and the Netherlands (39.9 %) [22]. However, in Brazil, we found that the group of CSs before labor (group 2b) impacted more on the contribution of term nulliparous women (14.9 %).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The same authors also pointed out that the proportion of this group in the population was similar between institutions, reinforcing the hypothesis that there are variations in the CS rate in this group that affect the overall rate. In our study, the proportion of groups 1 and 2 combined was 39 %, similar to that found in Latin America (36.4 %) [31], France (38.2 %) [21], Canada (39.7 %) [30] and the Netherlands (39.9 %) [22]. However, in Brazil, we found that the group of CSs before labor (group 2b) impacted more on the contribution of term nulliparous women (14.9 %).…”
Section: Discussionsupporting
confidence: 88%
“…The current analysis of CS by Robson classification revealed, as with other studies, that the nulliparous group, term, cephalic presentation is one that contributes most to the total rate of CS [21, 29, 30]. Analyzing nine institutions, Brennan et al [29] showed that 98 % of institutional variation in the CS rate may be attributed to this group, which contributed to over 30 % of CSs performed in France and the Netherlands [21, 22].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations